Population fluctuations of Cerithidea decollata (Gastropoda: Potamididae) in mangrove habitats of the St Lucia Estuary, South Africa. Issue 4 (2nd October 2018) - Raw, JL; Rishworth, GM; Perissinotto, R; Adams, JB
Abstract : Mangrove macrobenthos species are used as ecological indicators as they are sensitive to changes in sediment properties. In this study, the population density of the common mangrove whelk Cerithidea decollata was assessed during different environmental conditions in the St Lucia Estuary, South Africa. Previously, this species was found to persist through both hypersaline and freshwater-dominated conditions. The natural variability in C. decollata populations could provide information on the potential for this widespread species to be used as an ecological indicator in mangroves. We found that snail population density as well as sediment conductivity, moisture content and organic content differed between three mangrove sites that were monitored between 2010 and 2015. The relationship between snail population density and physicochemical characteristics of the sediment was therefore investigated using a mixed-effects model, and sediment conductivity was found to be the best predictor of C. decollata abundance. The resistance of this species to environmental variability could inform on resilience to ecological shifts, which is important when measuring responses associated with climate change.